2010
DOI: 10.2466/pms.110.2.603-612
|View full text |Cite
|
Sign up to set email alerts
|

Imitation of Modeled Manipulation of Objects by Children and Adults

Abstract: Prior studies have investigated imitation by extracting a hierarchy of goals from the key elements of action models. The theoretical model is that all ages practice a method of imitation in which goal or target elements are more easily imitated correctly, while nontarget elements are not. The present study compared error responses among 32 children and 32 adults when imitating an action model for manipulating concrete objects constructed of five elements. The results indicated that the elements for which error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…These findings contrast with evidence that 2-and 3-year-olds imitate the details of the model's actions more precisely when they have not received prior information about the final action goal (Carpenter et al, 2002;Williamson & Markman, 2006). Because encoding and reproducing observed actions puts high demands on young children's information processing (Mizuguchi et al, 2010), it would be interesting to study how exactly communicative cues help children of different ages to identify the relevant parts of an action demonstration.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…These findings contrast with evidence that 2-and 3-year-olds imitate the details of the model's actions more precisely when they have not received prior information about the final action goal (Carpenter et al, 2002;Williamson & Markman, 2006). Because encoding and reproducing observed actions puts high demands on young children's information processing (Mizuguchi et al, 2010), it would be interesting to study how exactly communicative cues help children of different ages to identify the relevant parts of an action demonstration.…”
Section: Discussionmentioning
confidence: 77%
“…For preschoolers, the preference for the goal in the presence, and for the movement in the absence, of target objects occurred from 3 to 6 years of age, with no significant differences between the age groups (Mizuguchi, Sugimura, & Deguchi, 2009;Perra & Gattis, 2008). Likewise, although 4-to 6-year-olds had a higher overall error rate than adults, the response patterns were comparable in children and adults (Mizuguchi, Suzuki, Sugimura, & Deguchi, 2010; see also Wohlschläger et al, 2003).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although there is not a great deal of research on imitation and overimitation among older children and adults, recent studies have suggested that adult imitation looks rather similar to imitation in children (Mizuguchi, Suzuki, Sugimura, & Deguchi, 2010), and in some cases adults will overimitate at rates even higher than those of children (Custance, Prato Previde, Spiezio, Rigamonti, & Poli, 2006;McGuigan et al, 2011;see also Nielsen & Tomaselli, 2010, where older children from multiple cultures were more likely to demonstrate overimitation than younger children). The current experiments are particularly concerned with whether or not participants of varying ages will be induced to imitate an action that is questionable, but that is presented as the appropriate way to achieve a goal.…”
Section: Introductionmentioning
confidence: 93%
“…For example, a movement model could be sequenced as follows: picking up the glue stick with the right hand, turning it right, tapping on the right side of the right cup, and placing the glue stick on the right side. This is in keeping with the movement model of Mizuguchi, Suzuki, Sugimura, and Deguchi (2010). The five elements were systematically combined to configure 32 movement models.…”
Section: Stimuli and Apparatusmentioning
confidence: 99%